Efeitos da administração única de doses intermediárias de pilocarpina nos comportamentos relacionados com ansiedade e depressão em camundongos swiss - Souza , Fernanda Maria Araujo de (2018)
Anxiety and depression disorders present genetic and neurobiological similarity, and both are a serious public health problem. Recent studies suggest the single administration of subconvulsant doses of pilocarpine (PILO) as animal model for the study of anxiety. However, an important criterion for developing animal models to study psychopathology involves establishing the validity of the model as a true representation of the processes being studied. Therefore, the present study aimed to evaluate the short- and long-term behavioral effects of a single administration of intermediates doses of PILO on the behavior of male and female Swiss mice submitted to different anxiety and depression tests. Animals were treated with scopolamine methylbromide (1 mg/Kg, s.c.) and, after 30 min, with PILO (75, 150 and 350 mg/Kg, i.p.) or Saline (NaCl 0,9%). Within 1.5h of the administration of PILO, the behavioral seizures were scored according to the Racine’s scale. Twenty-four hours or 30 days after the last treatment, animals were submitted to different anxiety [elevated plus maze (EPM) and light-dark box (LDB)], locomotion [open field test (OFT) and rota-rod (RR)] and depression [forced swim test (FST)] tests. The cortical and hippocampal electroencephalography (EEG) activity of female mice 24h after the treatment with PILO was also recorded. Our results demonstrated that all doses of PILO display alterations in the Racine’s scale. However, only the animals that had a stage less than 3 on the Racine´s scale (PILO 75 and 150 mg/Kg) were submitted to behavioral tests. The administration of PILO 75 mg/Kg reduced the frequency of entries (male) and the percentage of time (female) in the open arms of EPM, 24h after the treatment, indicating an anxiogenic-like effect. In LDB, PILO 75 also reduced the time spent in the light compartment (female) 30 days after treatment, indicating an anxiogenic-like effect too. In FST, administration of PILO 75 mg/Kg decreased the immobility time 24 h (male and female) and increased 30 days (female) after the treatment, indicating an antidepressant and depressive-like effects respectively. In contrast, the same dose increased the immobility time 30 days after the treatment, indicating a depressive-like behavior. No motor change was found in the OF and RR tests after administration of PILO 75 mg/Kg, as well as no alterations in the cortical EEG record after 24h. Treatment with PILO 150 mg/kg no changed any of the parameters in the different behavioral tests. Further studies are necessary to extend the validation of this animal model of anxiety, such as predictive validity. Our results found in the anxiety tests corroborate and extend previous literature data, which indicate the single administration of subconvulsivant doses of PILO as an anxiety model. For the first time, TNF results demonstrated a short antidepressive-like and a long depressive-like effects. Further studies needed necessary to extend the validation of this animal model of anxiety